2018
DOI: 10.1101/299420
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Myricetin Attenuates LPS-induced Inflammation in RAW 264.7 Macrophages and Mouse Models

Abstract: Background: Myricetin has been demonstrated to inhibit inflammation in a variety of diseases, but little

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Inflammation caused by IFN-γ was reported to be suppressed due to the regulatory matory cytokines . The inhibition of inflammation related genes as observed in the present study were in line with an earlier report, where the exposure to myricetin before LPS induction decreased the inflammatory activity in RAW264.7 macrophages [19]. This antiinflammatory effect may due myricetin capacity to suppress pro-inflammatory mediators' production by inhibiting NF-κB and STAT-1 signals pathways.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Inflammation caused by IFN-γ was reported to be suppressed due to the regulatory matory cytokines . The inhibition of inflammation related genes as observed in the present study were in line with an earlier report, where the exposure to myricetin before LPS induction decreased the inflammatory activity in RAW264.7 macrophages [19]. This antiinflammatory effect may due myricetin capacity to suppress pro-inflammatory mediators' production by inhibiting NF-κB and STAT-1 signals pathways.…”
Section: Discussionsupporting
confidence: 93%
“…The EZ-Cytox cell viability assay kit was used and cytotoxicity of RAW264.7 macrophages was not shown [18]. Houa et al had also reported that RAW264.7 macrophages exposed to LPS demonstrated no cytotoxicity following MTT assay when pretreated with 25 μM of myricetin [19]. The protective effects of mac be due to their inherent biological properties and may also be attributed to the rich presence of hydroxyl groups in myricetin chemical structure [20].…”
Section: Discussionmentioning
confidence: 99%
“…Other flavonoids and their anti-inflammatory and cancer-prevention properties are summarized in Table 1. [190] Paw Edema Mice and THP-1 (together) Inhibits Cox-2; STAT3 and NF-κB Inhibit inflammation [191] Brain Injury and neuroinflammation Rats Inhibits STAT3 and NF-κB p65 Inhibit inflammation [189] Fisetin Hypoxia NCI-H157 Inhibit HIF 1-α and STAT3 Prevents hypoxia [192] Hydrogen peroxide-induced oxidative stress HaCaT Inhibits iNOS, Cox-2, IL-1β, IL-6, and TNF-α Inhibit inflammation [193] Diabetic cardiomyopathy Rats Restores SOD and CAT; inhibits IL-1β, IL-6, and TNF-α; inhibits caspase-3, Bax, and Bax/Bcl-2 ratio Inhibit inflammation and apoptosis [194] Myricetin LPS-induced Inflammation Mice and RAW 264.7 Inhibits NF-κB p65 and AKT activation Inhibit inflammation [195] Colonic…”
Section: Daidzeinmentioning
confidence: 99%
“…The health benefits of Myr have been thoroughly investigated in over the last decade. Currently, Myr is known display the following biological properties: antioxidant (8), antimicrobial (9), antiviral (10), anti-inflammatory (11), anti-tumor (12), analgesic (13), hepatoprotective (14), hypoglycemic (15), hypolipidemic (16), cardioprotective (17), and neurological damage inhibition (18). Recently, the cardioprotective role of Myr has attracted attention from the research community due to its potential clinical impact (Fig.…”
Section: Biological Sources and Functions Of Myricetinmentioning
confidence: 99%